2022
DOI: 10.3389/fimmu.2022.1056750
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of signature genes and association with immune cells infiltration in pediatric septic shock

Abstract: BackgroundEarly diagnosis of septic shock in children is critical for prognosis. This study committed to investigate the signature genes and their connection with immune cells in pediatric septic shock.MethodsWe screened a dataset of children with septic shock from the GEO database and analyzed differentially expressed genes (DEGs). Functional enrichment analysis was performed for these DEGs. Weighted gene co-expression network analysis (WCGNA) was used to screen the key modules. Least absolute shrinkage and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
(69 reference statements)
2
12
0
Order By: Relevance
“…Fan et al 27 . recently analysed a dataset of children with septic shock compared to healthy controls to search DEGs and they confirmed the results observed by Liang et al 24 …”
Section: Methodssupporting
confidence: 60%
See 3 more Smart Citations
“…Fan et al 27 . recently analysed a dataset of children with septic shock compared to healthy controls to search DEGs and they confirmed the results observed by Liang et al 24 …”
Section: Methodssupporting
confidence: 60%
“…25 Similarly, Xie et al 26 found 160 upregulated genes and 61 downregulated genes in children with sepsis; the upregulated genes included sucrose metabolism, osteoclast differentiation and tumour necrosis factor (TNF) pathway. 26 Fan et al 27 recently analysed a dataset of children with septic shock compared to healthy controls to search DEGs and they confirmed the results observed by Liang et al 24 ; they also found an activation of genes related to secretory granule lumen, cytoplasmatic vesicle lumen, vesicle lumen and carbohydrate binding and endopeptidase activity. These genes were in patients with shock sepsis and not upregulated in healthy controls, suggesting a potential role in forecasting children with shock sepsis.…”
Section: Sepsissupporting
confidence: 64%
See 2 more Smart Citations
“…We employed the GSEA computational method to assess the statistical significance of a preselected gene set (15)(16)(17)(18). Following correlation analysis, we generated an initial list of gene categories.…”
Section: Gsea Analysismentioning
confidence: 99%